The relationship between physical exercise and social adjustment in Chinese university students: the sequential mediating effect of peer attachment and self-esteem - Xing, Zhi; Ge, ChunYan (Frontiers in Psychology, 2025)
Regular physical exercise is well-documented for its advantages that extend beyond physical health, notably influencing mental and social well-being. This study examines the correlation between physical exercise and social adjustment in Chinese university students (N = 672), with peer attachment and self-esteem acting as significant mediators. The analysis revealed a significant indirect effect through peer attachment (effect = 0.0376, 95% CI [0.0091, 0.0588]), self-esteem (effect = 0.2101, 95% CI [0.2730, 0.3690]), and a sequential mediation pathway (effect = 0.0055, 95% CI [0.0023, 0.0224]). Physical activity promotes social ties by encouraging peer bonding, which subsequently facilitates social adaptation. Moreover, self-esteem, a crucial element of psychological resilience, mediates the relationship between physical exercise and social adaptation. Importantly, a sequential mediation pathway—peer attachment—self-esteem—social adjustment—was supported, suggesting that peer relationships enhance self-esteem, which in turn improves social adaptation. This ordering aligns with theories emphasizing the influence of social feedback on self-concept (e.g., Reflected Appraisals Theory, Sociometer Theory). These findings underscore the comprehensive advantages of physical activity and support efforts to promote exercise in academic settings to facilitate student well-being and psychosocial development.